Social Origins of Dictatorships: Elite Networks and Political Transitions in Haiti - NAIDU, SURESH; ROBINSON, JAMES A.; YOUNG, LAUREN E. (The American political science review, 2021)
Existing theories of democratic reversals emphasize that elites mount actions like coups when democracy is particularly threatening to their interests. However, existing theory has been largely silent on the role of elite social networks, which interact with economic incentives and may facilitate antidemocratic collective action. We develop a model where coups generate rents for elites and show that the effort an elite puts into a coup is increasing in their network centrality. We empirically explore the model using an original dataset of Haitian elite networks that we linked to firm-level data. We show that central families were more likely to be accused of participating in the 1991 coup against the democratic Aristide government. We then find that the retail prices of staple goods that are imported by such elites differentially increase during subsequent periods of nondemocracy. Our results suggest that elite social structure is an important factor in democratic reversals.